1992
DOI: 10.1128/aem.58.5.1699-1704.1992
|View full text |Cite
|
Sign up to set email alerts
|

Acyloin formation by benzoylformate decarboxylase from Pseudomonas putida

Abstract: Whole cells and cell extracts of Pseudomonas putida grown in a medium containing ammonium mandelate have the capacity to produce the acyloin compound 2-hydroxypropiophenone when incubated with benzoylformate and acetaldehyde. Benzaldehyde and benzyl alcohol were formed as reaction by-products. The enantiomeric excess of the 2-hydroxypropiophenone product was found to be 91 to 92%. The absolute configuration of the enzymatically prepared product at the carbinol carbon was found to be S. The thiamine PP1-linked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 28 publications
2
29
1
Order By: Relevance
“…Pp BFD is an exceptional ThDP‐dependent enzyme, because it catalyses the formation of ( S )‐2‐hydroxy‐1‐phenylpropan‐1‐one (HPP) from benzaldehyde and acetaldehyde. This is one of the very few known S ‐selective reactions (92% enantiomeric excess [ ee ]) catalysed by this otherwise R ‐selective class of enzymes [46]. BFD further allows access to various ( S )‐HPP analogues based on the carboligation of acetaldehyde with different aromatic, heteroaromatic, cyclic aliphatic as well as olefinic aldehydes [28,29].…”
Section: Enzyme Engineering and In Vitro High‐throughput Screeningmentioning
confidence: 99%
“…Pp BFD is an exceptional ThDP‐dependent enzyme, because it catalyses the formation of ( S )‐2‐hydroxy‐1‐phenylpropan‐1‐one (HPP) from benzaldehyde and acetaldehyde. This is one of the very few known S ‐selective reactions (92% enantiomeric excess [ ee ]) catalysed by this otherwise R ‐selective class of enzymes [46]. BFD further allows access to various ( S )‐HPP analogues based on the carboligation of acetaldehyde with different aromatic, heteroaromatic, cyclic aliphatic as well as olefinic aldehydes [28,29].…”
Section: Enzyme Engineering and In Vitro High‐throughput Screeningmentioning
confidence: 99%
“…2 BAL catalyzes the cleavage of aromatic 2‐hydroxy ketones like benzoin, thereby allowing P. fluorescens to grow on media with benzoin as the only carbon source 3. 4 In 1991, Wilcocks and Ward first described a BFD‐catalyzed carboligase reaction that yielded 2‐hydroxypropiophenone (2‐HPP), by using benzoylformate and acetaldehyde as substrates 5. Further studies revealed that both BFD612 and BAL9, 1319 are able to catalyze the carboligation of a broad range of aldehydes; this makes them valuable catalysts for bioorganic syntheses.…”
Section: Introductionmentioning
confidence: 99%
“…Wilcocks and Ward reported the carboligase activity of BFD from P. putida for the first time, introducing the catalyst as an efficient alternative for the enantioselective synthesis of (S)-2hydroxyketones. 14 Its stereoselectivity is highly dependent on the structure of the substrate aldehydes. 15 For synthetic purposes, the enzyme also accepts aldehydes as donors, instead of R-ketoacids, to give the corresponding acyloins with (S)-configuration.…”
Section: Introductionmentioning
confidence: 99%